2017
DOI: 10.1186/s12860-017-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

External magnetic field promotes homing of magnetized stem cells following subcutaneous injection

Abstract: BackgroundMesenchymal stem cells (MSCs) are multipotent stromal cells that have the ability to self-renew and migrate to sites of pathology. In vivo tracking of MSCs provides insights into both, the underlying mechanisms of MSC transformation and their potential as gene delivery vehicles. The aim of our study was to assess the ability of superparamagnetic iron oxide nanoparticles (SPIONs)-labeled Wharton’s Jelly of the human umbilical cord-derived MSCs (WJ-MSCs) to carry the green fluorescent protein (GFP) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
(28 reference statements)
3
19
0
1
Order By: Relevance
“…Numerous studies have described flow cytometric evaluation of MSC surface markers in order to assess the differentiation potential of MSCs following nanoparticle internalization. 35,[45][46][47][48][49] In agreement with our findings, their results consistently reported no effects on surface-marker expression or osteogenic and adipogenic differentiation ability. These results showed that nanoparticlelabeling did not alter MSC differentiation or characteristics higher than 50 µg/mL did not enhance cell-uptake efficiency, at 100 µg/mL, the nanoparticles tended to aggregate in the culture medium and adhere to the plate.…”
Section: Characterization Of Mscs Loaded With Iron Oxide Nanoparticlessupporting
confidence: 90%
See 1 more Smart Citation
“…Numerous studies have described flow cytometric evaluation of MSC surface markers in order to assess the differentiation potential of MSCs following nanoparticle internalization. 35,[45][46][47][48][49] In agreement with our findings, their results consistently reported no effects on surface-marker expression or osteogenic and adipogenic differentiation ability. These results showed that nanoparticlelabeling did not alter MSC differentiation or characteristics higher than 50 µg/mL did not enhance cell-uptake efficiency, at 100 µg/mL, the nanoparticles tended to aggregate in the culture medium and adhere to the plate.…”
Section: Characterization Of Mscs Loaded With Iron Oxide Nanoparticlessupporting
confidence: 90%
“…Additionally, these represent the first findings of nanoparticles not only promoting CXCR4 expression, 24 but also increasing levels of the migration-related proteins c-Met and CCR1 in MSCs. Although some studies showed that noninvasive EMFs can increase nanoparticleinternalized MSC homing following an intra-arterial or intravenous injection, [34][35][36] there have been no reports showing a similar effect in the absence of EMFs in vivo. However, static magnetic fields can affect MSC viability, 34 proliferation, 37 differentiation capacity, 38 colony formation, 39 and extracellular vesicle secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Cytometric analyses of MNP-treated T cells showed that APS-MNPs caused no differences in the expression levels of important cell surface markers such as CD62L, CD44, CD11a or CCR7 in Jurkat and primary T cell. These data are in consonance with previous reports showing that MNPs have no significant effect on the expression levels of surface markers of a variety of cells [6266]. MNPs can trigger cellular activation in some cases [39, 67, 68] but this is mostly due to the nanoparticle design [69].…”
Section: Discussionsupporting
confidence: 91%
“…A sine qua non condition for MNP-based targeting strategies in ACT to be effective is that the effector lymphoid cells retain their function when loaded with MNPs. Several studies consistently indicate that the expression of surface markers is not significantly affected by MNP presence in a wide variety of cells including lymphoid cells [71,72,78,80,96,[127][128][129]. It thus appears that minimally functionalized MNP (i.e., with a simple chemical coating that allows stable colloidal suspension) do not significantly alter the activity of lymphoid cells.…”
Section: In Vitro Functionality In Mnp-loaded Lymphoid Cellsmentioning
confidence: 98%